Genetic dissection of a key dynamic growth period QTL for source–sink-related traits and its breeding application potential in wheat - Meng Yuan; Hongke Ding; Yunkai Yue; Chuanliang Zhang; Yuze Wang; Dandan Zhang; Shipeng Li; Ruiqi Nie; Jia Liu; Yanchuan Huang; Jinyu Han; Sufu Deng; et al. (Theoretical and Applied Genetics, 2026)

High temperature superconducting single photon detectors based on ultrathin MgB2 single-crystalline nanowires - Miao Ma; Minyan Zhao; Huimin Zhang; Ying Han; Xinwei Cai; Yan Zhang; Zizhao Gan; Shaohua Liu; Hao Li; Yuze Wang; Ying Chen; Xiaoqing Zheng; et al. (Science Bulletin, 2026)

Realization of elastic Weyl semimetal phases with skyrmion spin textures - Yuang Pan; Liang Si; Miao Yang; Ning Han; Li Zhang; Qiaolu Chen; Rui Zhao; Fujia Chen; Yudong Ren; Wenhao Li; Yuze Hu; Mingyu Tong; et al. (Science Bulletin, 2026)

Catalytic oxidative depolymerization of lignin into oligomers with multifunctional plant growth regulation in low dose - Yuze Zhao; Guanhua Wang; Yunmeng Luo; Yu Han; Wenhui Li; Yutong Zhao; Ning Wang; Wenjie Sui; Dongmin Li; Chuanling Si (Bioresource Technology, 2026)

Mechanistic insights and application of SS/MS/C/CaO₂ composite for the simultaneous removal of ammonia nitrogen and multiple antibiotics - Jie Zhao; Chang Lu; Junzhao Liu; Yuze Han; Xiuwen Li; Jun Li; Wentao Li; Hongbin Xu; Jingqing Gao; Aimin Li; Shuqing An (Water Research, 2026)

Simultaneous Removal of Nitrate and Typical Antibiotics Using Fe/MS/C Composite: Performance, Mechanism, Ecological Impact, and Practical Application - Jie Zhao; Junzhao Liu; Yuze Han; Chang Lu; Jun Li; Wentao Li; Hongbin Xu; Jingqing Gao; Aimin Li (Water Research, 2026)

Source apportionment and eco-health risk assessment of antibiotics in Gehu lake rivers: DOM fluorescence and microbial community responses - Jie Zhao; Xun Chen; Junzhao Liu; Yuze Han; Wentao Li; Aimin Li; Jun Li (Process Safety and Environmental Protection, 2026)

Unveiling the black box: Multi-omics reveal how biochar supercharges synthetic biofilms for superior bioremediation - Bo Zhang; Xiaoying Hu; Lu Han; Zhen Guo; Yongqi Liu; Huiyao Li; Yuze He; Tianyu Liu; Qingyuan Pan; Yi Mu; Jianhua Qu; Hongqi Yu; et al. (Journal of Hazardous Materials, 2026)

Gold nanoparticles recovered from e-waste by one-dimensional covalent organic framework for highly efficient reduction of nitrophenols - Wenping Yao; Bangdi Ge; Yuze Chen; Wenyu Jiao; Hao Han; Xiaowei Song; Zhiqiang Liang (Chemical Engineering Journal, 2025)

TFAP2A-regulated CRNDE enhances colon cancer progression and chemoresistance via RIPK3 interaction - Xin Gao; Yanming Huang; Tonghui Wei; Jingmin Xue; Filippov Iurii; Laishou Yang; Liying Wang; Hao Li; Genshen Mo; Yuze Huang; Haonan Xie; Hang Wang; et al. (Functional & Integrative Genomics, 2025)

In-situ remediation efficiency and mechanism of tylosin contaminated soil with biochar immobilized degrading enzyme - Bo Zhang; Xiaoying Hu; Zhen Guo; Jianhua Qu; Yuze He; Lu Han; Juntong Kou; Hongqi Yu; Jiuxuan Lian; Ying Zhang (Journal of Hazardous Materials, 2025)

External carbon sources shape the distinction of advanced nitrogen removal system: Insights into organic matters and microbial characteristics - Yuze Han; Jie Zhao; Yufeng Liao; Yechao Tian; Wentao Li; Aimin Li (Journal of Environmental Chemical Engineering, 2025)

Sterilized protective immunity induced by DAM and DAM+ in mouse models for both VACV and MPXV - Zhengrong Gao; Tingting Zheng; Jiahao Wu; Haoyi Ding; Jia Lu; Jiahui Si; Yuze Xu; Hao Liu; Guocan Yu; Renyi Ma; Jianxun Qi; Yunfei Zhao; et al. (Science Bulletin, 2025)

Environmental high-risk efflux pumps mediate concurrent enhancement of resistance and virulence in reclaimed water from urban wastewater treatment plants - Shanqi Shen; Zhong He; Siya Zhao; Zezhang Zhu; Xinyi Wang; Yechao Tian; Yuze Han; Min Hu; Chang Lu; Aimin Li (Journal of Hazardous Materials, 2025)

Mediated self-assembled gold nanoclusters with mesoporous silica particles to boost fluorescence for enhanced on-site monitoring of organophosphate pesticides - Shun Wang; Yaqing Han; Mengdi Su; Hao Wang; Yuze Chen; Baoling Huang; Qian Bai; Mengke Wang (Food Chemistry, 2025)

Enhancing CH4 hydrate storage efficiency using advanced porous nanofluids - Meng Han; Ying Teng; Bin Wang; Yinlong Li; Pengfei Wang; Senyou An; Yun Li; Yuze Wang; Songbai Han; Jinlong Zhu (Chemical Engineering Journal, 2025)

Microbial life-history strategies and particulate organic carbon mediate formation of microbial necromass carbon and stabilization in response to biochar addition - Yeye Zhang; Tao Wang; Chun Yan; Yuze Li; Fei Mo; Juan Han (Science of The Total Environment, 2024)

Effects of different alkyl chain lengths on excess properties of CO2-1-Butyl-1-methyl-pyrrolidinebis(trifluoromethanesulfonyl)imide, CO2-1-hexyl-1-methylpyrrolidinium bis(trifluoromethanesulfonyl)imide, CO2-1-octyl-1-methylpyrrolidinium bis(trifluoromethanesulfonyl)imide systems - Lijuan He; Jianzi Yang; Yuze Han; Dahua Yu; Zhong Zhou (International Journal of Refrigeration, 2024)

Hydrogen purification via hydrate-based methods: Insights into H2-CO2-CO hydrate structures, thermodynamics, and kinetics - Ying Teng; Yinlong Li; Ting Huang; Yiqi Chen; Pengfei Wang; Bin Wang; Senyou An; Yun Li; Songbai Han; Jinlong Zhu; Yuze Wang; Bin Chen; et al. (Gas Science and Engineering, 2024)

Effects of enzyme-induced carbonate precipitation technique on multiple heavy metals immobilization and unconfined compressive strength improvement of contaminated sand - Yi Bian; Yanbo Chen; Liangtong Zhan; Haowen Guo; Han Ke; Yuze Wang; Qingyang Wang; Yufeng Gao; Yunqi Gao (Science of The Total Environment, 2024)

Utilizing WFSim to Investigate the Impact of Optimal Wind Farm Layout and Inter-Field Wake on Average Power - Guohao Li; Lidong Zhang; Duanmei Zhang; Shiyu Yang; Yuze Zhao; Yongzheng Tao; Jie Han; Yanwei Wang; Tengyu Zhang (Journal of Marine Science and Engineering, 2024)
This paper presents a comprehensive study on optimizing wind farm efficiency by controlling wake effects using the WFSim dynamic simulation model. Focusing on five key factors—yaw wind turbine position, yaw angle, wind farm spacing, longitudinal wind turbine spacing, and yaw rate—we qualitatively analyze their individual and combined impact on the wind farm’s wake behavior and mechanical load. Through a quantitative approach using the orthogonal test method, we assess each factor’s influence on the farm’s overall power output. The findings prioritize the following factors in terms of their effect on power output: yaw wind turbine position, yaw angle, wind farm spacing, longitudinal spacing, and yaw rate. Most significantly, this study identifies optimal working conditions for maximizing the wind farm’s average power output. These conditions include a wind turbine longitudinal spacing of 7.0D, a wind farm spacing of 15.0D, a yaw angle of 30°, and a yaw rate of 0.0122 rad/s, with the first and second rows of turbines in a yaw state. Under these optimized conditions, the wind farm’s average power output is enhanced to 35.19 MW, marking an increase of 2.86 MW compared to the farm’s original configuration. Additionally, this paper offers an analysis of wake deflection under these optimal conditions, providing valuable insights for the design and management of more efficient wind farms.

Occurrence, distribution and potential environmental risks of pollutants in aquaculture ponds during pond cleaning in Taihu Lake Basin, China - Jie Zhao; Yuze Han; Junzhao Liu; Baoju Li; Jun Li; Wentao Li; Peng Shi; Yang Pan; Aimin Li (Science of The Total Environment, 2024)

Correlation Between Blood Cadmium Levels and Platelet Characteristics, As Well As Their Impact on Susceptibility to Coronary Heart Disease: Findings from NHANES 2005–2018 Data - Jichen Ci; Yuze Zhai; Benjun Wang; Weiwei Han; Bianfang Yu; Fan An (Cardiovascular Toxicology, 2024)

Visual study of methane hydrate kinetics in a microfluidic chip: Effect of the resins extracted from the crude oil - Yu Feng; Yuze Han; Yuxin Jia; Xin Lv; Qingping Li; Yanzhen Liu; Lunxiang Zhang; Jiafei Zhao; Lei Yang; Yongchen Song (Fuel, 2024)

The multifunctionality of soil aggregates is related to the complexity of aggregate microbial community during afforestation - Qi Zhang; Hanyu Liu; Yueqi Liang; Yaoyue Liang; Yongtao Zhao; Zhengchen Wang; Yuze Li; Weichao Liu; Xing Wang; Gaihe Yang; Chengjie Ren; Wei Zhang; et al. (CATENA, 2024)

Formation and dissociation of CO2 hydrates in porous media in the presence of clay suspensions - Yu Feng; Yang Zhao; Yuze Han; Yanzhen Liu; Lunxiang Zhang; Jiafei Zhao; Lei Yang; Yongchen Song (Chemical Engineering Journal, 2023)

Gas hydrate nucleation and growth in a micro-reactor: Effect of individual component separated from the crude oil in the South China Sea - Yu Feng; Man Li; Yuze Han; Qingping Li; Xin Lv; Jiafei Zhao; Lei Yang; Yanzhen Liu; Yongchen Song (Chemical Engineering Journal, 2023)

Vapor-liquid equilibrium experiment and prediction of excess property of new working pair CO2-[BMP][Tf2N] in absorption refrigeration system - Lijuan He; Wenxuan Yang; Yuze Han; Yunfeng Liu; Huitong Zhao; Guang Jin (International Journal of Refrigeration, 2023)

Fast and accurate measurement of spectral emissivity with a portable field infrared spectrometer: ancillary equipment and methods - YuZe Zhang; Li Ni; Hua Wu; XiaoGuang Jiang; Ying Han (International Journal of Remote Sensing, 2019)

Carbon dioxide fixation by the seaweed Gracilaria lemaneiformis in integrated multi-trophic aquaculture with the scallop Chlamys farreri in Sanggou Bay, China - Tingting Han; Zengjie Jiang; Jianguang Fang; Jihong Zhang; Yuze Mao; Jian Zou; Yao Huang; Dongzhe Wang (Aquaculture International, 2013)